Evaluation of Muscle Quality of Monopterus Albus from Different Sources - Tao MAO, Jinhua GAN, Yali YU, Lixue DONG, Lang ZHANG, Tao ZHANG,Bo CHENG, Li HE (Forest Chemicals Review)
Five kinds of Monopterus albus from different sources were used as research objects to study the differences of muscle nutrition and texture characteristics, and to evaluate the quality of M. albus, so as to provide reference for purchasing M. albus. The results showed that there were significant differences in crude fat content among the five different sources of M. albus (P < 0.05). The highest content was domesticated M. albus, and the lowest content was Chinese wild M. albus. There were no significant differences in water and crude fat content (P > 0.05). Among the 5 M. albus, there were 17 kinds of amino acids, among which, M. albus from Vietnam had the highest content of essential amino acids (7.95%), and M. albus from Bangladesh had the highest content of total amino acids (19.79%), with no significant difference in flavor amino acid amino acids (P > 0.05). All the five species of M. albus were in line with the high quality protein of FAO/WHO model. The contents of saturated fatty acids and polyunsaturated fatty acids were higher than those of domestic M. albus, and the content of monounsat urated fatty acids was significantly lower than that of domestic M. albus (P < 0.05). The hardness, masticability, elasticity and viscosity of wild M. albus in China were the highest, and its taste was the best. The results showed that the five different sources of M. albus had their own nutritional characteristics. By comprehensive comparison, the domesticated M. albus contained higher crude protein, complete amino acids, rich kinds of fatty acids, and taste similar to that of wild M. albus, and had higher edible value.